Pengaruh Tingkat Pendidikan, Pendapatan, dan Pengetahuan Keuangan terhadap Perilaku Pengelolaan Keuangan Keluarga di Desa Jeding Kecamatan Sanankulon Kabupaten Blitar - Laila, Maya Nur; Yudiantoro, Deny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted with the aim of seeing how the level of education, income and financial knowledge affect family management behavior. This study uses a Quantitative approach and uses primary data in it. The population used is families who live in Jeding Village, Sanankulon District, Blitar Regency. Sampling using purposive sampling technique and obtained 100 samples to be studied. The data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, T test and F test. With this research, it can be seen that: a) there is no significant effect on the level of education on family financial management behavior, b) there is no significant effect on income on family financial management behavior, c) there is a significant effect on financial knowledge on family financial management behavior, d) there is a significant effect on the level of education, income, and financial knowledge simultaneously on family financial management behavior Keywords: Family, Management, Education, Income, Financial Knowledge.